Combination of Vascular Intervention Surgery and Free Tissue Transfer for Critical Diabetic Limb Salvage. (February 2016) - Chou, Chieh; Kuo, Pao-Jen; Chen, Yen-Chou; Huang, Shu-Hung; Chang, Chih-Hau; Wu, Yi-Chia; Lee, Su-Shin; Lai, Cheng-Sheng; Lin, Sin-Daw; Chang, Kao-Ping; Kuo, Yur-Ren
Abstract : Background: Complex, nontraumatic diabetic foot ulcers with peripheral vascular compromise often lead to extensive lower-limb amputation. The aim of this study is to determine the outcome of combined vascular intervention and free tissue transfer for critical diabetic limb salvage. Materials and Methods: A total of 26 consecutive diabetic patients with 28 legs with diabetic foot ulcers who underwent limb salvage with a combination of revascularization (bypass surgery or endovascular angioplasty) and free flap transfers were reviewed. There were 14 male and 12 female patients. The average age was 58.8 years (range, 35–85 years). Amputation-free survival and complete wound healing were defined as the primary endpoints. All preoperative and postoperative data were retrospectively analyzed. Results: Thirty flaps were used for reconstruction in 28 legs, including 21 free anterolateral thigh (ALT) perforator flaps, 3 ALT myocutaneous flaps, 5 gracilis muscle flaps, and 1 latissimus dorsi muscle flap. All flaps used end-to-side anastomoses for the recipient artery and end-to-end anastomoses for the recipient vein. The overall flap success rate was 90% (27/30). Two flaps failed completely because of severe arteriosclerosis, which resulted in anastomosed vessel thrombosis. New flaps were applied in both cases after debridement and trimming of necrotic tissue. One flap failed because of restenosis and inadequate perfusion combined with severe infection, resulting in pedicle thrombosis. A below-knee amputation was subsequently performed. Seven flaps exhibited a partial loss, including 6 ALT perforator flaps and 1 latissimus dorsi flap, because of inadequate margin perfusion. After debridement, the flap revision and wound care, 5 flaps healed uneventfully without additional intervention. The remaining 2 ALT perforator flaps required debridement with a skin graft. The limb-salvage rates were 92.8% after 1 year and 89.2% after 5 years. Conclusions: The combination of peripheral arterial intervention and free tissue transfer resulted in successful wound healing and limb salvage instead of amputation in select diabetic patients with difficult-to-heal wounds.